The polyimage poetics in Ibsen’s late plays - Yuli, Wang (Nordlit, 2015)
The unique poetics of polyimage implied in Ibsen’s late plays can be excavated with aesthetic reading. The term polyimage is coined to describe Ibsen’s original design in aesthetic form and ingenious realm in aesthetic reaction in his late plays; that is, beyond an imagery realm, another imagery realm exists, which construct a deep vision of significance. In each of the excellent late plays, what Ibsen creates is one or more veiled holistic imagery realms in addition to an ordinary entire imagery realm perceived by most audiences. The “layers of imagery realm” result from Ibsen’s “double self-examinations”, including self-examination of soul and of art. It is these “double self-examinations” that make polyimage possible in his late plays and generates the attribute of “meta-art” in these works. Compared with polyphony in Dostoevsky’s novels, the polyimage in Ibsen’s late plays contains a unique modernity, which is of great significance to modern artistic creation.